МЕТАФОРАЛАР ТАРЖИМАСИ ТАҲЛИЛИДА КОНТЕКСТНИНГ ЎРНИ - Рофиева, Г.Ю. (SCIENCE and SOCIETY, 2020)
The article is devoted to the analysis of a stylistic device metaphor in the literary text. The author also studies the issues of translation of metaphor and role of the context in translation. On the basis of the analysis of extracts from the works of the famous Uzbek writers and their translation into French, it has been shown metaphors, reflecting the national culture.